Screening Level of Gross Alpha and Beta Activities in Building Materials - Elassaad Jemii (Journal of Chemistry)
The objective of the present study is the screening of the gross alpha and gross beta activity of some building materials commercialized in Saudi Arabia. The measurements were carried out using a gas flow proportional counter. The study has shown that the gross alpha activity ranged between 0.21 and 8.27 Bq/kg with an average activity of about 1.96 Bq/kg, whereas the gross beta activity ranged between 6.47 and 276.47 Bq/kg with an average activity of about 65.27 Bq/kg. The obtained values of gross alpha and beta activities are in the worldwide range and no significant activity was observed that accentuate the attention, which show that no radiation risks come from these building materials and, therefore, from their origin areas.